Investigating EFL Graduate Students’ Academic Writing Apprehension and Their Volition as Control Strategies - Averina, Elleny (Fakultas Ilmu Budaya, Universitas Brawijaya, 2024)
Even though studies on academic writing apprehension at graduate and post-graduate levels have been conducted, few of them examined the strategies used by the students to down-regulate their academic writing apprehension by involving volitional strategies. Thus, to fill the gap in the literature, this study aimed to investigate graduate students’ academic apprehension level and their volitional strategies. This study employed a mixed-method design by utilizing a close-ended questionnaire and semi-structured interview as the techniques to collect the data. The participants of the study were thirty graduate students of one of the private universities in Yogyakarta, Indonesia. Results showed that, firstly, the participants had a moderate level of academic writing apprehension, with batch 2021 scoring slightly higher than batch 2020. Secondly, the participants used volition as a control strategy for down-regulating their apprehension. From the components of volitional strategies, self-efficacy enhancement was reported to be dominantly employed by the participants followed by stress-reducing actions, and negative-based incentives.